The reflection of [tex]f(x) = 3\cdot x + 2[/tex] in the x-axis is [tex]g(x) = -3\cdot x - 2[/tex]. The function used to derive [tex]g(x)[/tex] is: [tex]g(x) = -f(x)[/tex]. (Correct choice: [tex]g(x) = -3\cdot x - 2[/tex])
Mathematically speaking, a reflection in the x-axis is defined by the following expression:
[tex]g(x) = -f(x)[/tex] (1)
Where:
If we know that [tex]f(x) = 3\cdot x + 2[/tex], then the expression for [tex]g(x)[/tex] is:
[tex]g(x) = - (3\cdot x + 2)[/tex]
[tex]g(x) = -3\cdot x - 2[/tex]
The reflection of [tex]f(x) = 3\cdot x + 2[/tex] in the x-axis is [tex]g(x) = -3\cdot x - 2[/tex]. The function used to derive [tex]g(x)[/tex] is: [tex]g(x) = -f(x)[/tex].
We kindly invite to see this question on reflections: https://brainly.com/question/23558898